Hib Vaccines: Past, Present, and Future Perspectives - Adi Essam Zarei; Hussein A. Almehdar; Elrashdy M. Redwan (Journal of Immunology Research)
Haemophilus influenzae type b (Hib) causes many severe diseases, including epiglottitis, pneumonia, sepsis, and meningitis. In developed countries, the annual incidence of meningitis caused by bacteria is approximately 5–10 cases per population of 100,000. The Hib conjugate vaccine is considered protective and safe. Adjuvants, molecules that can enhance and/or regulate the fundamental immunogenicity of an antigen, comprise a wide range of diverse compounds. While earlier developments of adjuvants created effective products, there is still a need to create new generations, rationally designed based on recent discoveries in immunology, mainly in innate immunity. Many factors may play a role in the immunogenicity of Hib conjugate vaccines, such as the polysaccharides and proteins carrier used in vaccine construction, as well as the method of conjugation. A Hib conjugate vaccine has been constructed via chemical synthesis of a Hib saccharide antigen. Two models of carbohydrate-protein conjugate have been established, the single ended model (terminal amination-single method) and cross-linked lattice matrix (dual amination method). Increased knowledge in the fields of immunology, molecular biology, glycobiology, glycoimmunology, and the biology of infectious microorganisms has led to a dramatic increase in vaccine efficacy.